Caesar and the Plebeians: The Ambivalent Alliance in Plutarch’s Lives and Shakespeare’s Julius Caesar - Mufeed Al-Abdullah (An Overview of Literature, Language and Education Research Vol. 7, 2024)
Dramatizing the alliance of Caesar and the commons, or the Caesarians, from Plutarch, Shakespeare traverses a contradictory historical situation. This article is a comparative study of the nature of the alliance between Caesar and the masses in Plutarch’s Lives and Shakespeare’s Julius Caesar. It demonstrates that Plutarch pays a lot of attention to mapping the nature and the roots of the bond between Caesar and his supporters. Caesar exploits the mobs to gain power against other patricians. In fact, Caesar heeds the whims of the mobs and their interests, but he humiliates and degrades his fellow senators. His ambition is to transcend above his peers and gather full power in Rome. His means of achieving this dream is the alignment with the masses that help him thwart any senatorial decisions against him. Plutarch, however, portrays the Roman masses as clear, judgmental, and aware of Caesar’s political maneuvers. They review their alliance with him in light of his political activities. In contrast, Shakespeare starts Julius Caesar with the last war Caesar fought in his life and thus shows no interest in mapping the roots of his alliance with the people of Rome. He rather depicts the plebeians as naïve and gullible to the tricks and manipulations of Caesar. They show a taste of political awareness that is not accentuated in the play. Nevertheless, Shakespeare brings to the fore the power of rhetoric and its magical influence in formulating the perceptions and views of men. It was concluded that the Roman biography presents the mobs as sophisticated and judgmental with clear views about politics and politicians, whereas the Elizabethan play presents them as corrupt, selfish, and fickle. In the play, the innovative writer introduces the two sequential orations that show the magical influence of language on the minds of men. The study helps the modern reader understand how Shakespeare employed stories and events from classical antiquity to develop his own themes and ideas of human interaction and social dynamics. He demonstrates the magical power of eloquence in influencing people by using the Roman story to cut through the underlying currents of human nature. Shakespeare’s viewpoint emphasizes the importance of language as a key subject.